PENGARUH KOMPOSISI CAMPURAN TERHADAP DURABIUTAS HIGH-FLOWABLE CONCRETE PADA PENGECORAN BETON DI RAW AH AIR - Slamet Widodo; Sri Haryono (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2003)
Concrete that used for under water construction need to be proportioned to spread readily and self consolidate. High Flowable Concrete (HFC) is a kind of High Performance Concrete (HPC) that able to spread readily (flowability more than 50 cm according to BS – 1881). This kind of concrete can be resulted by using higher water/binder ratio or adding some High Range Water Reducer (HRWR) agent. This reseacrh proposed to evaluate effects of water/binder ratio and High Range Water Reducer based on polycarboxylatether (Sika Viscocrete-5) dosage on fresh concrete properties, compressive strength and water absorption of underwater concrete. The research has done with o,40 and 0,45 water/binder ratio and 0.3, 0.6, 0.8, 1.0 and 1.3 percent of HRWR by total wight of binder. 30 cubes (15cm x15cm x15cm) of underwater concrete were used for absorption examination according to ASTM C-127-68 underwater concrete cylinders (Ø 15cm x 30cm) were investigated for compressive strength in 56 days. Test result indicates that HRWR based on polycarboxylatether could improve flowability up to 3.24 % for 0.4 water per binder ratio and 23.90 % for 0.45 w/c. High Range Water Reducer also improve durability of underwater concrete, indicates by the reduction of water absorption up to 11.11 % for 0.4 water per binder ratio and 18.28 for 0.45 water per binder ratio. Better durability of underwater concrete could be obtained by reducing the value of water per binder ratio that indicated by lower water absorption.